Vou procurar o melhor lá dentro : vivências e memórias de crianças e adolescentes na FUNABEM (Viçosa, 1964-1989) - Campos, Gisélia Maria (2007)
The teenagers and children that lived between the years of 1964 and 1989 at the Fundação Nacional do Bem-Estar do Menor the FUNABEM institute in Viçosa are the social essence of this research. While working with their memories, I ve tried to understand the meaning of their habits and experiences in the institution, and also outside, in other areas of sociability. I have discussed about the meaning of living at FUNABEM and at the city of Viçosa, in that historical moment, with the purpose of rethink about the needy childhood and needy adolescence problem in our country. At that direction, I ve worked with very distinct social-nature sources, such as: handbooks, occurrences books and periodicals produced by the institution, letters, minutes of Viçosa s city-hall, the Viçosa s newspaper Folha da Mata and also oral narratives and photos. The theoretical-methodological suppositions of contemporary English Marxism, of cultural studies related to the subjects action in history and to the culture as a way of socially living and fighting, were paths that gave direction to this research.